Leveraging Social Media Marketing and Local Wisdom to Enhance Tourist Visit Intentions in Community-Based Tourism - Angger Bondan Widiantoro (Arthatama: Journal of Business Management and Accounting, 2023)
Local wisdom is identified as a critical mediating factor, amplifying Social Media Marketing's effectiveness. Cultural elements, such as festivals and traditions, showcased through social media, promote authenticity and build trust, enhancing tourists’ attachment to destinations. This integration creates a positive destination image and motivates both initial visits and recommendations. This study aims to explore how Social Media Marketing (SMM) influences tourists' intention to visit community-based tourism (CBT) destinations and assess the mediating role of local wisdom in this relationship. This study examines the role of Social Media Marketing (SMM) in influencing tourists' intention to visit community-based tourism (CBT) destinations. The method used in this study is by using a qualitative and descriptive approach. The study highlights that visit intention occurs in two phases: pre-visit and post-visit, both influenced by destination image and emotional resonance. Findings suggest that integrating cultural elements into SMM strategies can drive sustainable CBT development and long-term loyalty. This research provides valuable insights into the strategic use of SMM and local wisdom to strengthen tourist engagement and visit intentions.